The sportivization process of a martial art: the karate - Oliveira, Marcelo Alberto de; Lopes, Jefferson Campos; Sonoda-Nunes, Ricardo João; Figueiredo, Abel Aurélio Abreu (Revista de Artes Marciales Asiáticas, 2019)
This study addresses the historical trajectory of karate, particularly in relation to the processes that favored its inclusion as one of the five modalities that will debut at the 2020 Olympic Games in Tokyo, Japan. The literature review was the methodology used in this research. Several attempts and efforts were identified to enable karate to join as a sport in the Olympic Games. It was concluded that the agents (federation leaders, presidents, coaches and athletes), along with institutions (clubs, companies, government, among others) were involved in a process that aimed to meet the requirements of the International Olympic Committee. Thus, it is possible to observe various transformations in the development of this modality that gave shape to what karate has today, which has made it a rookie modality being conditioned by market interests.